On the correlation of the primary breakup length with fuel temperature in pressure swirl nozzle. (15th December 2019) - Rezaei, Shahnaz; Vashahi, Foad; Ryu, Gyongwon; Lee, Jeekeun
Abstract: This work is focused on the effect of viscosity on the estimation of liquid sheet thickness and breakup length of a pressure swirl nozzle that is undergoing fuel temperature variation. The pressure swirl nozzle tested in this study was developed for aviation gas turbine engines, where the ignition characteristics included an importantly low-temperature environment. Jet A-1 aviation fuel was used for various injection pressures at different fuel temperatures. With the aid of a laser sheet planar imaging, instantaneous spatial spray images were acquired. In lower fuel temperature cases, the fuel viscosity increased, resulting in a slowing of the liquid sheet breakup process. An increased mass flowrate and a decreased spray cone angle were observed at lower fuel temperatures and fixed injection pressures. With a decrease in fuel temperature, the primary breakup length and secondary breakup length increased dramatically. A newly proposed expression for predicting the primary breakup length of the liquid sheet and accounting for viscosity effects with the change of fuel temperature is presented.